Evaluation of therapeutic gain for fractionated carbon-ion radiotherapy using the tumor growth delay and crypt survival assays. Issue 2 (November 2015) - Yoshida, Yukari; Ando, Koichi; Ando, Ken; Murata, Kazutoshi; Yoshimoto, Yuya; Musha, Atsushi; Kubo, Nobuteru; Kawamura, Hidemasa; Koike, Sachiko; Uzawa, Akiko; Takahashi, Takeo; Ohno, Tatsuya; et al.
Abstract: Background and purpose: The aim of the study was to evaluate the therapeutic gain of carbon ion (C-ion) radiotherapy using a mouse model. Materials and methods: Transplanted fibrosarcoma (NFSa) growing in C3H/He mice and murine small intestine were irradiated with 290 MeV/nucleon C-ion beams (C-ions) in 1–12 fractions separated by 4 h. The cell killing efficiencies of C-ions were measured using jejunum crypt survival and tumor growth delay (TGD) assays. Results: The equieffect dose for crypt survival and TGD increased with increasing number of fractions after X-rays and 20 keV/μm C-ions, whereas TGD after 77 keV/μm C-ions rather decreased. Crypts showed stronger LET-dependent increase in α terms than the tumor while β terms less depended on LET irrespective of tissues. Therapeutic gain factor, i.e., a ratio of tumor RBE over crypt RBE, of 77 keV/μm C-ions was more than unity at any doses while that of 20 keV/μm C-ions increased with an increase in dose per fraction. Conclusions: These specific data imply that use of large dose per fraction would be suitable for C-ion radiotherapy irrespective of LET from the point of view of therapeutic gain, though small dose per fraction by high-LET radiation decreases total dose for tumor.